Cyber Threat Analysis to Personal Data in the Digital Era - A. Hamdani; Bilqis Sofia; Farah Salsabilla Aulia Rahmah; Ika Ariyanti (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
The development of information technology provides convenience in daily life, but at the same time increases the risk of cyber threats to users' personal data. This study aims to analyze the level of user vulnerability to digital threats and the factors that influence personal data security, including the role of digital literacy and user behavior. The method used is descriptive qualitative, collecting data through a literature review, structured observation of digital device usage patterns, and semi-structured interviews with a number of selected users. The results show that weak password management practices, the tendency to share personal information, and low awareness of suspicious links or applications are the main causes of data vulnerability. The level of attention to vulnerability evaluation, security awareness, and security audits remains low, even though users are aware of potential threats. These findings confirm that digital literacy and user behavior play a crucial role in reducing risks. Therefore, improving cybersecurity education, implementing safe digital practices, and conducting regular security audits and evaluations are necessary to effectively protect personal data and build a safer digital culture.